2010
DOI: 10.1071/mf09312
|View full text |Cite
|
Sign up to set email alerts
|

Changes in organic-matter dynamics and physicochemistry, associated with riparian vegetation loss and river regulation in floodplain wetlands of the Murray River, Australia

Abstract: Extensive clearing of floodplain forests potentially reduces organic matter available to floodplain wetlands. Furthermore, on rivers regulated to provide irrigation water in summer, floodplain wetlands that were previously inundated in spring, now flood in summer/autumn. In the Murray–Darling Basin, Australia, this has changed the timing of organic matter entering the aquatic phase, since leaf fall peaks in summer. Field surveys and mesocosm experiments on floodplain wetlands on the River Murray revealed faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Towns 1985;Boulton and Lake 1992;McMaster and Bond 2008), flooding temperate floodplain rivers and wetlands (e.g. Richardson 1981;cited in McKinnon 1995;McKinnon 1995;Howitt et al 2007;McNeil and Closs 2007;Watkins et al 2010), and in tropical floodplain rivers (e.g. Bishop 1980;Townsend and Edwards 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Towns 1985;Boulton and Lake 1992;McMaster and Bond 2008), flooding temperate floodplain rivers and wetlands (e.g. Richardson 1981;cited in McKinnon 1995;McKinnon 1995;Howitt et al 2007;McNeil and Closs 2007;Watkins et al 2010), and in tropical floodplain rivers (e.g. Bishop 1980;Townsend and Edwards 2003).…”
Section: Introductionmentioning
confidence: 98%
“…leaf, bark, twigs; O'Connell et al 2000) and between aged and fresh leaf litter (Baldwin 1999). Watkins et al (2010) showed that the timing of inundation was critical to Australian river floodplains as litter fall peaks over summer and aging of river red gum leaves increased their ability to be decomposed. The significantly lower response to leachate addition in February 2011 is likely ) were assessed with a two-way ANOVA, using site and fraction factors with Bonferroni post-tests (critical P ¼ 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…River regulation also has an impact on riparian vegetation (Bren 1993;Watkins et al 2010) and, coupled with intensive agricultural clearing, greatly reduces the allochthonous organic matter (OM) inputs into rivers (Watkins et al 2010) thus altering the carbon dynamics necessary in maintaining stream ecosystem health and biodiversity .…”
Section: Introductionmentioning
confidence: 99%